Forestland Changes from Agricultural Practices in 03 Villages of Hiem District, Houaphan Province - THINNAKHONE, Bounsack; INTHAPANYA, Sangkhom; CHANNANG, Bounheung (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this study was to study the forestland changes from being used for agricultural production by the people during a period of 5 years (2018-2022); socio-economic factors that lead to changes, the ways to solve problems in 03 villages: Huaphu, Phonsaat and Napauk village. The study method used the planet satellite image translation from 2018 and the satellite image data (Sentinel-2) recording data from 2022 by translating the meaning of the land at each time by using the Geoprocessing intersect tool in the Arc GIS program to find the change point and distinguish the type of land, for socio-economic factors and solutions were used the interview form within The data were analysis to: descriptive statistics to describe personal data, economic and social factors, analysis using frequency, percentage, mean and standard deviation; hypothesis testing to find the relationship between the independent variable and the dependent variable using the statistical value of multiple regression analysis. The results showed that: The analysis of changes in forestland from its use in agricultural production found that: the forest cover in 2022 has changed compared to 2018, namely: Huaphu village showed that the forest area over five years has decreased by 113,318 ha, equal to 2.44%, but the areas of ​​agricultural land increased by 113.64 ha, equally to 2.45%; Phonsaat village over five years had increased by 145.03 ha, equal to 1.30%, while the area of ​​agricultural land decreased by 145.03 ha, equally to 1.30%; In Napauk village, the forestland has changed to 805.89 ha, equal to 10.09%, and agricultural land has changed to 805.89 ha, equally to 10.09 % respectively. The personal, economic and social factors that affect the changing in the use of agricultural land were: the place of origin of the family when all constant values ​​change in the use of their agricultural land and in the same direction, which it's can explain that when the place of origin of the people in the village changes, it was affecting the use of the people's farmland in the same direction. Aage: when all the constant values changed the use of the people's farmland by changing in the opposite direction. Promotion: when all the fixed values ​​of the variables of a promotion funding changes the use of the people's farmland by changing in the opposite direction. Occupation: when all the constant values ​​of the occupation variables change in people's agricultural land use changes by changing in the opposite direction. However, the guidelines for solving the problem of land use changed and found that all participants must be in the solution: 1) public sectors such as decentralization, law enforcement, and land use planning to be detailed and clearly labelled, 2) village governing bodies such as village regulations, publicizing regulations, laws and legislation to the people, creating careers for the people, solving village disputes, and 3) people themselves such as having a conscience, having knowledge, implementing regulations, laws and following the socio-economic development plan of the village.